An active power control strategy for a DFIG-based wind farm to depress the subsynchronous resonance of a power system. (July 2015) - Bin, Zhao; Hui, Li; Mingyu, Wang; Yaojun, Chen; Shengquan, Liu; Dong, Yang; Chao, Yang; Yaogang, Hu; Zhe, Chen; ,
Highlights: Proposed a new control strategy for a DFIG-based wind farm to depress SSR. The analytical expression of the damping coefficient was derived to design the SSR auxiliary damping controller. Utilizing genetic algorithm to optimize the PID phase compensation parameters of the SSR auxiliary damping controller. Abstract: This study presents a novel auxiliary damping control strategy to depress subsynchronous resonance (SSR) oscillations in nearby turbine generators. In the proposed control strategy, SSR damping is achieved by adding turbine generator speed as a supplementary signal at the active power loop of the rotor-side converter (RSC) of doubly-fed induction generator (DFIG)-based wind farms. To design the SSR auxiliary damping controller, a transfer function between turbine generator speed and the output active power of the wind farms was introduced to derive the analytical expression of the damping coefficient. Then the damping effect of the active power of the DFIG-based wind farms was analyzed, and the phase range to obtain positive damping was determined. Next, the PID phase compensation parameters of the auxiliary damping controller were optimized by genetic algorithm to obtain the optimum damping in the entire subsynchronous frequency band. The last, the validity and effectiveness of the proposed auxiliary damping control were demonstrated on a modified version of the IEEE first benchmark model by time domain simulation analysis with the use of DigSILENT/PowerFactory.